IMPACT OF MODERNIZATION ON PAKISTANI WOMEN - Menhas, Rashid (Innovare Journal of Social Sciences, 2014)
Modernization is a multidimensional concept initiated by industrialization. Before industrialization, society based upon traditional social institutions. Modernization brought about changes in every segment of society. Modernization has both negative and positive impact on society. In Pakistan, modernization has great impact on young female. In present scenario of modernization in Pakistan, it has negative impact on young generation. Female is part and parcel in every society and played a vital role in development process. According to feminist perspective, females should be given equal rights to men and not limited to homes. Islam is also granted women rights which are considered necessary for women development. But it is the habit of West that they attributed each and every good aspects of life with them. They have made women only sexual object for their leisure and decline their respect. Women think that sexual freedom plays an important role in their development. These negative impacts have been found among Pakistani women. Present study was conducted in Bahria Town Islamabad, Pakistan. Main objective of this study was to investigate the impact of modernization regarding their lifestyle. A sample of hundred females was selected through convient sampling technique. A well designed questionnaire was used for the collection of data. Results of this study reveal that majority of the females 42% prefer arrange marriage, large majority the females 42% wear jeans and 50% females reported that vulgarity is prevailing among females.